Assessing pain in the postoperative period: Analgesia Nociception Index(TM)versus pupillometry - Charier, David (Br J Anaesth, 2019)
BACKGROUND: Potential methods for objective assessment of postoperative pain include the Analgesia Nociception Index™ (ANI), a real-time index of the parasympathetic tone, the pupillary light reflex (PLR), and the variation coefficient of pupillary diameter (VCPD), a measure of pupillary diameter (PD) fluctuations. Until now, the literature is divided as to their respective accuracy magnitudes for assessing a patient's pain. The VCPD has been demonstrated to strongly correlate with pain in an obstetrical population. However, the pain induced by obstetrical labour is different, given its intermittent nature, than the pain observed during the postoperative period. The aim of the current study was to compare the respective values of these variables at VAS scores ≥4. METHODS: After approval by the Ethics Committee, 345 patients aged on average 50 (SD 17) yr (range: 18–91 yr) of age were included. The protocols of general anaesthesia and postoperative analgesia were left to the anaesthetist's discretion. Some 40 min after tracheal intubation, VAS, ANI, PD, PLR, and VCPD values were recorded. RESULTS: VCPD correlates more strongly (r=0.78) with pain as assessed with the VAS than ANI (r=−0.15). PD and PLR are not statistically correlated with VAS. The ability of VCPD to assess the pain of patients (VAS≥4) is strong [area under the curve (AUC): 0.92, confidence interval (CI): 0.89–0.95], and better than for ANI (AUC: 0.39, CI: 0.33–0.45). CONCLUSIONS: Our study suggests that VCPD could be a useful tool for monitoring pain in conscious patients during the postoperative period. CLINICAL TRIAL REGISTRATION: NCT 03267979.